Are obesity, ACPAs and periodontitis conditions that influence the risk of developing rheumatoid arthritis in first-degree relatives? (2020)
The aim of this study was to investigate the body mass index (BMI), anti-citrullinated protein antibodies (ACPAs) status and the presence of periodontitis and IgG-1/IgG-2 antibodies against Porphyromonas gingivalis (Pg) in the first-degree relatives (FDRs) of rheumatoid arthritis (RA) patients and compare these variables with a control group of healthy individuals from the general population. In total, 100 FDR individuals and 200 healthy controls matched by age and gender were included. Rheumatologic and periodontal assessment was performed, and the presence of ACPAs and anti-P. gingivalis antibodies was evaluated. Groupwise comparisons were analysed using the McNemar and Wilcoxon tests. A conditional logistic regression analysis was performed to establish the associations between BMI, ACPAs and periodontitis in both groups. In the FDR group, 70% of the subjects were female, with a mean age of 37.3 ± 13 years. Obesity was observed in 17 and 7% of the FDRs and controls, respectively. ACPAs were found in 7% of the FDRs vs. 2.5% of the controls. Periodontitis was diagnosed in 79 and 56% of the FDRs and controls, respectively. Among the FDRs, 15% had severe periodontitis. There were associations in the FDR group related to the presence of obesity (OR 2.93, 95% CI 1.03–8.28), ACPAs (OR 2.45, 95% CI 0.7–8.32) and periodontitis (OR 3.70 95% CI 1.89–7.29). Regarding anti-P. gingivalis antibodies and smoking history, no differences were found between the groups. Obesity, ACPAs and periodontitis (diagnosis and severity) can be considered as relevant conditions associated with the development of RA in FDRs.